One thing I know [large type] - Isaac, Kara (Center Point Large Print, 2019)
"A fresh, heartfelt romance involving a case of mistaken identity when a ghostwriter masquerades as a relationship expert and the man who is determined to expose her holds not only the key to her success, but also her heart"--